The roles of Non Timber Forest Products in the development of community forestry in Menoreh Hills (A case of Hargorejo Village, Kokap, Kulon Progo Regency, Yogyakarta) - Maria Palmolina (Jurnal Ilmu Kehutanan)
Development of Non-Timber Forest Products (NTFPs) in various forestry development program that promotes the function of environmental, social, economic, and culture of local communities is expected to create sustainability. One of the forestry development programs are Community Forest (HKm). This study aimed to determine the role of NTFPs in community forest development which was done in Menoreh Hills in Hargorejo’s Village, Kokap, Kulon Progo’s Regency. Data were collected in January until June 2013 with in-depth interviews to 10 informers and by questioners to 35 members of the group of farmers who had arable land in HKm. The dominant type of timber plants were teak, mahogany, and acacia. Further, the NTFPs plants grown were fruit crops (banana, jackfruit), food crops (cassava, corn, soybeans, peanuts), and herbs (ginger, turmeric, temulawak). The management of HKm was conducted independently by DAMAR fondation. In addition to the condition of being green and cool environment (66% of respondents said the village environment becomes greener and cooler), increased water discharge (76% of respondents expressed a lot of water supplies), the positive impact of community forest management in Hargorejo’s Village was also the contribution to the household economy of farmers (a reduction in the percentage of less well economic conditions of farmers from 80% to 52% after the access HKm).